Deskripsi Faktor – Faktor Kecemasan Orang Tua pada Anak Pre Operasi Di Ruang Bedah RSUP DR. M.Djamil Padang : Description of Parental Anxiety Factors in Preoperative Children in the Surgical Room of Dr. M.Djamil Padang Hospital - Musymiratul Fauziah; Dwi Novrianda; Hermalinda (Fakultas Keperawatan Universitas Andalas, 2016)
Anxiety is the emotional response of preoperative most frequently reported in pre operative children, with a prevalence of up to 60% (Akdag et al, 2014). Preoperative anxiety is also felt by the parents of pre operative children. This study aimed to describe the anxiety factors of parent in pre operative children in the pediatric surgery room RSUP Dr. M. Djamil Padang. Type of research was quantitative research with cross sectional study. The sampling technique used accidental sampling with 30 samples. This research held from June 20 to July 30, 2016. Data were analyzed using univariate analysis. Analysis results showed that more than half (53,3%) of respondents were late adulthood, more than half (66,7%) of respondents were mothers, more than half (66,7%) of respondents had a high education, more than half (53,3%) of respondents did not work, more than half (53,3%) of respondents had low knowledge, more than half (56,7%) of respondents had personality type B, more than half (53,3%) of respondents received high support from family members, more than half of respondents received (53,3%) high support form nurses, and average anxiety of respondents was 15,6 and it showed moderate anxiety. Suggested to the nurses in pediatric surgery room to increase the information support like counseling face to face with the parents during the child is in preoperative period, so that can increase the knowledge of parents.